An Obligation of Corporate Criminal Liability in the Case of Non-Implementation of Occupational Health and Safety (OHS) - MALAU, Parningotan; SYAHRIN, Alvi (Journal of Advanced Research in Law and Economics, 2020)
Cases of industrial accidents occur as a result of corporations ignoring or not caring about the terms and conditions of occupational health and safety (OHS) according to Law Number 1 of 1970 concerning Occupational Safety (UUKK). The purpose of this research is to analyze the responsibility of corporate criminal liability if the OHS protection of workers/laborers is not implemented in the workplace. The research method used is legal research (normative juridical) with a statutory approach. The results of this study conclude that corporations must be liable for criminal liability for OHS workers' protection on the grounds that due to the bitter history of the conditions of Indonesian labor protection since the colonial era, protection is a concretization of Pancasila values, neglect of OHS protection is a violation of workers human rights at work, neglect of workers protection as an abuse of economic power and as a form of corporate crime. For the future, expectations this research contributed to knowledge and stakeholders aware of the importance of corporations burdened with criminal liability in the event that the protection of workers. Of personal skills, expected characteristics include the ability to protected workers and the ability to perform the renewal of the formulation of corporate criminal liability policies in accordance with the development of corporate punishment and living values in society.